2013
DOI: 10.1073/pnas.1215759110
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the repressor REST in uterine fibroids promotes aberrant G protein-coupled receptor 10 expression and activates mammalian target of rapamycin pathway

Abstract: Uterine fibroids (leiomyomas) are the most common tumors of the female reproductive tract, occurring in up to 77% of reproductiveaged women, yet molecular pathogenesis remains poorly understood. A role for atypically activated mammalian target of rapamycin (mTOR) pathway in the pathogenesis of uterine fibroids has been suggested in several studies. We identified that G protein-coupled receptor 10 [GPR10, a putative signaling protein upstream of the phosphoinositide 3-kinase-protein kinase B/AKT-mammalian targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 51 publications
(62 reference statements)
2
79
0
2
Order By: Relevance
“…We identified a high expression of PRLHR, the gene that encodes for this receptor in leiomyomas of the MED12 subtype. A recent study showed that up-regulation of PrRPR stimulates the proliferation of cultured primary human leiomyoma cells, and that transgenic mice overexpressing PRLHR develop myometrial hyperplasia with excessive extracellular matrix deposition (40).…”
Section: Discussionmentioning
confidence: 99%
“…We identified a high expression of PRLHR, the gene that encodes for this receptor in leiomyomas of the MED12 subtype. A recent study showed that up-regulation of PrRPR stimulates the proliferation of cultured primary human leiomyoma cells, and that transgenic mice overexpressing PRLHR develop myometrial hyperplasia with excessive extracellular matrix deposition (40).…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 also functions as a sensor of cellular nutrients, energy level and redox status. There are reports showing that mTORC1 can be activated by GPCRs, but it is not yet recognized as a canonical pathway (Musnier et al, 2010;del Toro et al, 2010;Wauson et al, 2012;Varghese et al, 2013). Three mechanisms of activation have been described: modulation of mTORC1 via transactivation of RTK/ PI3K/AKT by GPCRs and/or by MAP-kinase (Raf/MEK/ERK) signaling (Rozengurt 2007) and more recently, a direct interaction was discovered between the serotonin 5-HT(6) receptor and many proteins from the mTORC1 pathway, including the mTOR kinase itself (Meffre et al, 2012).…”
Section: The Importance Of the Redd1 Nt Domainmentioning
confidence: 99%
“…Immunohistochemistry previously demonstrated that NRSF/REST expression is significantly lower in breast cancer samples compared with normal and benign breast samples, and that knockdown of NRSF/REST expression by short hairpin RNA in MCF-7 human breast cancer cells resulted in an increase in cell proliferation, suppression of apoptosis and reduced sensitivity to anticancer drugs (20). Previous studies have also demonstrated the important function of NRSF/REST in the pathogenesis of uterine fibroids (21). However, the expression of NRSF/REST in liver tumors remains unclear.…”
Section: Introductionmentioning
confidence: 99%